La caries y placa bacteriana con relación a los aspectos sociofamiliares - Lobato Cabrera, Alisson Fernanda (2023)
ABSTRACT: The research work aimed to synthesize the updated theoretical positions on caries and plaque associated with socio-family aspects through a scientific bibliographic review, identify the most appropriate indices for the diagnosis of caries, contribute with the updated theory on the plaque index; to finally determine the relationship between caries and bacterial plaque with socio-family aspects. For the development of the research, articles were used from journals indexed through databases such as PubMed, Scielo, Elsevier, Google Scholar and Medigraphic were used in a period of 10 years, that is, from 2013 to 2023, where 59 quality publications were selected for the review process. As a result, it was determined that socio-family aspects are associated with caries and bacterial plaque, affecting the quality of life of people, among the problems that most affect the progression of this disease is the lack of knowledge for prevention and the economic factor that prevents people from regularly monitoring their oral health. The most widely used index for the detection of this disease is the CPOD index that describes decayed, missing and filled teeth, allowing the assessment of the patient's dental health. Dental plaque is also important to mention because it is the cause of the demineralization of the tooth structure when you do not have proper oral hygiene, causing periodontal diseases that lead to the loss of teeth.